DETERMINAN BUDGETARY SLACK (Pada Pemerintah Kota Langsa) - Indriani; Afrah Junita; Iqlima Azhar (Program Studi Akuntansi, Fakultas Ekonomi. Universitas Samudra, 2021)
This study aims to determine the Determinants of Budgetary Slack (In Langsa City Government). The research sample is all SKPK Langsa City. The data analysis method used in this research is multiple linear regression. Classical assumption test consisting of normality test, multicollinearity test, and heteroscedasticity test. The hypothesis test consists of t test, f test, and coefficient of determination test. The results of this study indicate that (1) role ambiguity has no significant effect on budgetary slack, (2) self-esteem has a significant effect on budgetary slack, (3) budgetary participation has a significant effect on budgetary slack.